EFEKTIVITAS KERJASAMA UNODC DAN PEMERINTAH KOLOMBIA DALAM MENANGANI MASALAH DRUG TRAFFICKING DI KOLOMBIA JANGKA WAKTU 1999-2017 - Nuharani Savitri; Soca Rizky Ayu Andari Andari; Tri Cahya Utama (Journal of International Relations Diponegoro, 2019)
Drug sales and planting are a form of crime that creates a real threat. This research is motivated by the number of drugs, namely cocaine which is planted in Colombia and smuggled to be sent to various countries of the world. These illegal actions led Colombia to become a country with high crime rates. Preventing crime related to drugs such as eradicating planting, and stopping drug sales is the duty of the Colombian government. But the Colombian government cannot implement it optimally so that they cooperates with UNODC. The collaboration between the Government of Colombia and UNODC is a solution to effectively eradicate the planting and distribution of drugs from Colombia. The main objective of this research is to see how effective the collaboration between UNODC and the Government of Colombia in dealing with drug trafficking issues in 1999-2017. Using the concept of effectiveness and the concept of cooperation in the regime in looking at cooperation, researchers are looking for answers to problems that question how effective collaboration between UNODC and the Colombian Government. Seeing the facts, cooperation between the two parties was declared to be less effective because despite there are developments in programs, the rate of increase in cocaine plants remained and the graph actually rose even more so in 2017